The Growth and Production of Three Sweet Potato Varieties as Affected by Dosage of Potassium Fertlizer on the Ultisols of Bengkulu Province - Taufiq Al-Qodri; Bambang Gonggo Murcitro; Alnoopri Alnopri; Prasetyo Prasetyo (Department of Soil Science, Faculty of Agriculture, University of Bengkulu, 2021)
This study aims to study the interaction between varieties and the correct dose of potassium fertilizer, determine the right dose of potassium fertilizer and the appropriate variety of sweet potato in Ultisol. In this study, the research design used was a completely randomized block design (RAKL) with two (2) factors with three replications. The first factor is three varieties of sweet potato, namely Cilembu, Atin 3, and Beta 1. The second factor is the dose of KCl fertilizer which consists of 4 levels of dosage, namely 0 kg ha-1, 150 kg ha-1, 300 kg ha-1, and 450 kg ha-1 KCl fertilizer. The results showed no significant interaction between the dose of KCl fertilizer and the three varieties of sweet potato. The Antin 3 variety produced the most extended tendril length compared to the other two varieties. The lowest number of branches was produced by Beta 1 variety. The Cilembu variety produced the most significant tuber weight per plot and estimated weight per plot. The Cilembu variety is proven to have the highest level of sweetness.